Pain Intensity (PI) and Quality of Life (QoL) in patients with Chronic Non-Cancer Pain (CNCP) receiving Medication Review – A Protocol. - Duarte, Nuno; Santos, Marlene; Pedraza, José (Proceedings of Research and Practice in Allied and Environmental Health, 2023)
Background: Chronic pain is defined by the International Association for the Study of Pain (IASP) as “pain that lasts or occurs for longer than 3 months” [1]. A recent prevalence study conducted in primary care units in Portugal found a 33,6% prevalence of chronic pain [2]. The study highlights a high prevalence of chronic pain patients while also identifying some characteristics and associated risk factors. In medication review with follow-up (MRF), care plans are developed with the patient’s agreement and recommendations regarding pharmacotherapy changes are discussed with physicians to optimize clinical outcomes [3]. Objective: Implementation of MRF in chronic non-cancer pain (CNCP) patients in primary care setting, and compare this intervention with standard care by assessing, its influence on pain intensity (PI), quality of life (QoL) and patient global impression (PGI). Methods: A randomized parallel study, with blinding to patients relative to interventions and blinding to assessment, consisting of two arms, the intervention where MRF will be conducted, and the “active placebo” which will comprise standard care. Outcomes are assessed by self-report using a numerical rating scale (NRS) for PI, the brief pain inventory for QoL and patient global impression of change scale for PGI (secondary outcome). Results: A PI improvement of 1,5 points in the NRS between-groups on average PI score from baseline until the end of the study, is defined as the minimal clinically relevant difference (MCRD). Standard deviation (SD) estimate was obtained based on interquartile range of a prevalence study on chronic pain in Portugal which gives an SD of 1,48 [4]. To detect the MCRD and considering the SD estimate, a confidence interval of 95% and a power size to detect effect of 80%, the sample size must be approximately 15 subjects for each arm (n=30) for a two-sided test. Conclusions: We hypothesized that these main outcomes will be different between groups, favoring the group receiving MRF.